EXTRACTION AND CHARACTERIZATION OF OIL FROM DATE PALM SEED (PHOENIX DACTYLEPHERA) USING N-HEXANE - Alexander David Onoja,; Usman, Salifu Oma; Abdullahi, Aminu Sezor; Jacob, Alifa David; Ocheme, Gabriel Wilson; Sheneni, Victor; Audu, Ali Salihu; Jimoh, Abdulazeez Enesi (FUDMA JOURNAL OF SCIENCES, 2023)
This research aimed to extract, characterize and identify oil components in date-palm seed  The date-palm were collected after eating several date-palm (seed). The extraction was undertaken with the aid of a soxhlet apparatus and a solvent hexane was selected based on the fact that it has a very low value of toxicity and A huge retraction rate. The particles gotten from were separate units from numbers i.e. 710um, 1mm and 2mm mesh size mesh size, which 40g each were measured and subjected to the extraction steps and the following values of oil were obtained: respectively: 363, 3.49 and 3.25 with the smallest particle size producing the highest yield. , While the result obtained from FTIR analysis showed the following functional group results CH2, C=O, C=C, C-C, C-O. In the Oil Extract the physicochemical indicates acid value: 2.55mg/g, peroxide value: 1.40mg/g, Saponification value: 80.50mg/g, iodine value: 83.31mg/g, free  fatty acid value: 6.71mg/g. However,  from this analysis date palm seed oil has high oil value compared to other edible vegetable oil.